Lexical-Semantic Expression Method Of Respectful Speech - Abduraxmonova Irodaxon Shuhratjon qizi (Periodica Journal, 2025)
This article discusses the expression of the meaning of respect in the Uzbek language through lexical-semantic means. Lexemes expressing respect, their place in the synonymous series, morphological and syntactic-stylistic features are analyzed. Also, expressions expressing respect in formal and informal speeches and the context of their use are studied
Keywords: expressions; meaning; synonymous